2008
DOI: 10.1001/archfaci.10.2.93
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Risk Factors for Pathologic Scarring After Burn Wounds

Abstract: To describe the clinical characteristics of postburn scars and determine the independent risk factors specific to these patients. While burns may generate widespread and disfiguring scars and have a dramatic influence on patient quality of life, the prevalence of postburn pathologic scarring is not well documented, and the impact of certain risk factors is poorly understood. Methods: A retrospective analysis was conducted of the clinical records of 703 patients (2440 anatomic burn sites) treated at the Turin B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
136
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(153 citation statements)
references
References 30 publications
7
136
1
4
Order By: Relevance
“…Among different studies on post burn scarring, the risk factors included dark skin, female sex, young age, burn site on neck and/or upper limbs, multiple surgical procedures, meshed skin graph, time to healing, and burn severity [31,32]. In this study female sex, young age, burn site on neck and/or upper limbs were also found more in the enrolled patients under this study.…”
Section: Discussionmentioning
confidence: 56%
“…Among different studies on post burn scarring, the risk factors included dark skin, female sex, young age, burn site on neck and/or upper limbs, multiple surgical procedures, meshed skin graph, time to healing, and burn severity [31,32]. In this study female sex, young age, burn site on neck and/or upper limbs were also found more in the enrolled patients under this study.…”
Section: Discussionmentioning
confidence: 56%
“…It is well accepted that scar maturation can take between 18 months and 3 years to fully establish, particularly in the presence of contracture release or reconstruction, so it not unreasonable that contracture management would also require a similar period of time to achieve functional goals [30][31][32]. Additionally, individual characteristics including age, gender, skin pigmentation, burn depth and presence of comorbidities are known to affect burn wound healing time [33][34][35]. Therefore the risk of developing circumoral scar tissue and subsequent contractures with restricted mouth opening is very specific to each individual.…”
Section: Discussionmentioning
confidence: 99%
“…The 2 patients who failed to meet the set functional criteria both possessed a number of characteristics known to be predictive of poorer outcome [33][34][35]. These features were female gender, widespread facial and neck grafting, graft failure and subsequent need for repeat grafting, in addition to dark skin pigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Burn treatment professionals agree that devastating aesthetic and functional problems result from scarring due to burn injuries. After burn wounds and grafts have healed, burn survivors are frequently disfigured, disabled, stigmatized, and shunned because of their scars (Gangemi et al, 2008). Studies suggest that in 32 to 67 percent of burn injuries, hypertrophic scarring is prevalent (Bombaro et al, 2003;Deovic, Koupilavia, & Brychta, 1999;Druecke et al, 2004;Spurr & Shakespeare, 1990).…”
Section: Available Knowledgementioning
confidence: 99%